Ability and willingness to work during COVID-19 pandemic:Perspectives of front-line hotel employees - Stergiou, Dimitrios P.; Farmaki, Anna (My University, 2021)
This research note reports the results of a qualitative study exploring front-line hotel employees’ views about working during the COVID-19 pandemic in order to identify factors that may influence their ability and willingness to report to work. Findings from online focus-groups reveal that front-line hotel employees generally felt a sense of duty to work during the pandemic. However, there were also a number of perceived barriers to working that impacted on this sense of duty. These emerged as barriers to ability and barriers to willingness, but the distinction is not clear-cut. Instead, most barriers seem to form a continuum ranging from negotiable barriers to insuperable barriers. Following this coneptualisation, the key to reducing absenteeism during the pandemic is likely to take remedial action so that barriers to willingness do not become perceived as barriers to ability to work. Practical implications towards this direction are offered.
Keywords: COVID-19; Pandemic; Crisis; Hotel employees; Absenteeism; Willingness to work